2021
DOI: 10.19101/ijatee.2021.874521
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review on student performance predictions

Abstract: Nowadays, many high school and higher educational systems generate a large number of student information through the learning management system, examination data, students' activities, library system, etc. [1]. This situation leads to increases in the volume and types of educational data in every institution. Machine learning (ML), learning analytics (LA), and data mining (DM) approaches have been widely used on educational data to predict students' performance. These approaches have shown that several techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In Nawang et al (2021) systematic literature review, the authors discussed the use of the EDM, LA, and ML to predict student's academic performance in secondary schools and higher educational institutions. This review provided an overview of the methods and algorithms that are used in the prediction and identified the features that have the most significant effects on their performance.…”
Section: Related Workmentioning
confidence: 99%
“…In Nawang et al (2021) systematic literature review, the authors discussed the use of the EDM, LA, and ML to predict student's academic performance in secondary schools and higher educational institutions. This review provided an overview of the methods and algorithms that are used in the prediction and identified the features that have the most significant effects on their performance.…”
Section: Related Workmentioning
confidence: 99%
“…On topic of student performance predictions which includes predicting students grades (tests, exams, quizzes, assignments, GPA) and attendance, (Nawang et al, 2021) analyzed 40 papers and found that this application of ML has been widely adopted in higher education. Regarding the most widely used techniques by researchers, the authors found that while Decision Tree, Random Forest, SVM, Artificial Neural Network (ANN) and Naïve Bayes (NB) were the most widely used techniques and it was Random Forest that proved to be the most accurate technique in predicting student performance.…”
Section: Theoritical Framework and Related Studiesmentioning
confidence: 99%
“…A wide range of data mining techniques has been employed for this purpose, each with its own strengths and limitations. A survey was conducted to provide a comprehensive overview of the intelligent models and paradigms used in education [12]. The survey identifies various challenges in predicting student performance, such as the high dimensionality of educational data, class imbalance, and the lack of labelled data.…”
Section: Related Workmentioning
confidence: 99%